KETIMPANGAN DISTRIBUSI PENERIMAAN RUMAH TANGGA PETANI KARET DI DESA MARGO MULYO KECAMATAN PONDOK KUBANG KABUPATEN BENGKULU TENGAH - Afif, Marzuki; Purwoko, Agus; Arianti, Nyayu Neti (Jurnal AGRISEP, 2016)
The purpose of this research are counting the revenue of rubber farming farmers, analyzing sources of household rubber farmer revenue, and analyzing the unequal distribution of household rubber farmer revenue. The location of this research was determine by deliberate consideration that the village Margo Mulyo has GAPOKTAN that active in building village and working for welfare farmers. Data used in this research is primary and secondary data. The results of this research show that the average revenue of rubber farmers is about Rp. 708.278/farmer/month. Based on contributions of farming revenue rubber gives 46 percent, the non farming rubber contribution gives 21 percent, contributions of revenue from non agricultural gives 32 percent. Gini Ratio for the revenue of households rubber farmers in the village Margo Mulyo of 0.45 explain that the unequal distribution of households revenue of the rubber farmers are at moderate level.